SUPREMACY AND STABILITY OF THE CONSTITUTION. LOYAL CONSTITUTIONAL BEHAVIOR OF PUBLIC AUTHORITIES - Marius ANDREESCU; Andra PURAN (Challenges of the Knowledge Society)
The procedure for amending the Constitution is extremely difficult, almost impossible in the current social and political context. The essence of a constitution is its stability over time because only in this way can ensure the stability of the entire normative system of a state, certainty and predictability of the conduct of the legal subjects but also to ensure the legal, political and economic stability of the social system as a whole. The obligation of the authorities, respectively of the parliament and of the executive to have a loyal constitutional conduct was for the first time stipulated in the jurisprudence of the French Constitutional Council, which is the constitutional court of France. This obligation is found in the attributions to interpret and apply the constitutional norms that the state authorities have. It is not limited to the simple requirement of legality of the acts and provisions of the rulers, i.e. to the formal observance of the law. In our opinion, the concern of the political class and state authorities in the current period, in relation to the current content of the Fundamental Law, should be oriented towards its correct interpretation and application and respect for the democratic finality of constitutional institutions. In order to consolidate the rule of law in Romania, even in the current normative form of the Constitution, it is necessary that political parties, especially those in power, all state authorities act or exercise their powers within the limits of loyal constitutional behavior and the democratic meanings of the Constitution, the Orthodox Christian traditions and values of the Romanian people, the rights and dignity of the person. In this study we analyze aspects of doctrine and jurisprudence of the concept of loyal constitutional behavior.